PENGARUH EFEKTIVITAS EFISIENSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN BADAN USAHA MILIK GAMPONG (BUMG) (Studi Pada Kecamatan Kluet Tengah Kabupaten Aceh Selatan) - Rima Melati; Nasrul kahfi Lubis; Nurlaila Hanum (Jurnal Mahasiswa Akuntansi Samudra, 2022)
This research was carried out in order to understand how much influence Effectiveness, Efficiency and Accountability had on the Management of Gampong-Owned Enterprises (BUMG) (a case study in Kluet Tengah District, South Aceh Regency). The population taken in this study are villages that have Gampong-Owned Enterprises (BUMG) as many as 11 villages. The sampling technique used is purposive sampling, purposive sampling is the determination of a sample based on the size used to determine something. To collect data, it was done by distributing questionnaires in the form of questions to 55 respondents and then the data obtained were analyzed using SPSS (Statistical Program for Social Science). The type of data used in this study is quantitative data and analyzed using multiple linear regression. The results in this study indicate that effectiveness has a positive and significant effect on the management of Gampong-Owned Enterprises (BUMG), efficiency also has a positive and significant effect on the management of Gampong-Owned Enterprises (BUMG), and accountability has a positive and significant effect on the management of BUMG.